1979
DOI: 10.1126/science.228395
|View full text |Cite
|
Sign up to set email alerts
|

Generation by Insulin of a Chemical Mediator That Controls Protein Phosphorylation and Dephosphorylation

Abstract: Deproteinized skeletal muscle extracts free of major nucleotides from control and insulin-treated rats were fractionated and assayed for inhibition of protein phosphorylation by cyclic adenosine monophosphate (AMP)-dependent and -independent protein kinases. A differential effect of insulin on a particular fraction was observed on cyclic AMP-dependent protein kinase but not on cyclic AMP-independent protein kinases. This fraction that inhibited cyclic AMP-dependent protein kinase also stimulated glycogen synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
92
1
2

Year Published

1980
1980
2001
2001

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 370 publications
(102 citation statements)
references
References 11 publications
7
92
1
2
Order By: Relevance
“…High concentrations of insulin increase bioactivity of the pH 1.3 IPG as well as the myo-inositol content of the IPG isolated from skeletal muscle [1,8] and liver [26]. The lack of increase in the serum pH 1.3 IPG in the present study could thus be due to an insufficient increase in the extracellular insulin concentration, suggesting differential sensitivities of different IPG generating/releasing systems to insulin.…”
Section: Discussioncontrasting
confidence: 41%
See 2 more Smart Citations
“…High concentrations of insulin increase bioactivity of the pH 1.3 IPG as well as the myo-inositol content of the IPG isolated from skeletal muscle [1,8] and liver [26]. The lack of increase in the serum pH 1.3 IPG in the present study could thus be due to an insufficient increase in the extracellular insulin concentration, suggesting differential sensitivities of different IPG generating/releasing systems to insulin.…”
Section: Discussioncontrasting
confidence: 41%
“…Bioactivity of the pH 1.3 IPG was determined by following PKA-dependent incorporation of 32 P from radioactive ATP into histone essentially as described earlier [1], with slight modifications. Mediator (20 To obtain further information on the components of the isolated bioactive fractions, nitrous acid exposure experiments were performed.…”
Section: Analyticalmentioning
confidence: 99%
See 1 more Smart Citation
“…However the same fraction activated a crude preparation of glycogen synthase phosphatase Z-fold [22]. These results are consistent with the conclusion drawn here; namely, that the primary site of insulin action is restricted to either cyclic AMPdependent protein kinase and/or protein pllosphatase-1.…”
Section: Discussionsupporting
confidence: 82%
“…It has been suggested that one or more chemical mediators are generated subsequent to this interaction and alter the activities of some insulin sensitive enzymes [7,8]. Several investigators suggest the possibility that insulin generated chemical mediators by activating an insulin-sensitive phospholipase C acting as a novel glycophospholipid [9][10][11].…”
Section: Introductionmentioning
confidence: 99%